Singapore-Malaysia Relations: Future Prospects - Han, David (2016)
Singapore-Malaysia relations have reached the best-ever period in their history. While the current generation of leaders has helped to improve relations institutional norms of diplomacy and mutual respect for each other’s interests are necessary to ensure strengthening of bilateral ties.